2018
DOI: 10.1111/jfpe.12924
|View full text |Cite
|
Sign up to set email alerts
|

On‐line rheology of pearl millet flours during extrusion: Effect of native amylose

Abstract: Pearl millet is a micro‐nutrient rich crop grown in arid regions of Asia and Africa. Millet based extruded products can ensure both food and economic security amongst these malnutrition prone areas. The effect of flour crystallinity and amylose content on the rheological attributes during thermo‐mechanical processing of pearl millet cultivars was determined using on‐line rheometer during twin‐screw extrusion. The shear strain measurements indicated shear thinning behavior which was modeled using modified Power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 31 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…Lipids involved in the complex formation with amylose are a novel Gulati et al, 2016;Hagenimana et al, 2006;Kharat et al, 2019;Rudra et al, 2018). Narang et al (2018) found a decreased WSI for pearl millet-based extruded snacks as the FM increased.…”
Section: Water Absorption Index and Water Solubility Indexmentioning
confidence: 99%
“…Lipids involved in the complex formation with amylose are a novel Gulati et al, 2016;Hagenimana et al, 2006;Kharat et al, 2019;Rudra et al, 2018). Narang et al (2018) found a decreased WSI for pearl millet-based extruded snacks as the FM increased.…”
Section: Water Absorption Index and Water Solubility Indexmentioning
confidence: 99%
“…Moisture also influences the elasticity characteristics of starchbased materials. During extrusion, in a high-pressure, high-temperature F I G U R E 1 Snacks according to coded variables of central composite experimental design: moisture (horizontal, X 1 ) and temperature (vertical, X 2 ) F I G U R E 2 Surface response of the specific volume of snacks environment, increased moisture reduces the elasticity of a starchbased material due to a change in the molecular structure of amylopectin, thereby reducing the expansion of the product and increasing its density, consequently decreasing its SV (Rudra et al, 2018). Maximum expansion is generally desirable for extruded snacks, as those with high expansion are crispier because the internal structure has larger cells with fine walls (Yagci & Gogus, 2009).…”
Section: Snack Expansion Propertiesmentioning
confidence: 99%
“…Moisture also influences the elasticity characteristics of starchmaterials. During extrusion, in a high-pressure, high-temperature tin, thereby reducing the expansion of the product and increasing its density, consequently decreasing its SV (Rudra et al, 2018). Maximum expansion is generally desirable for extruded snacks, as those with high expansion are crispier because the internal structure has larger cells with fine walls (Yagci & Gogus, 2009).…”
Section: Snack Expansion Propertiesmentioning
confidence: 99%
See 2 more Smart Citations